Exploring patient preference heterogeneity for pharmacological treatments for chronic pain: A latent class analysis. (8th January 2022) - Walsh, David A.; Boeri, Marco; Abraham, Lucy; Atkinson, Jo; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Hauber, Brett; Klein, Kathleen; Russo, Leo; Viktrup, Lars; Turk, Dennis
Abstract: Background: Several pharmaceutical treatments for chronic pain caused by osteoarthritis (OA) and chronic low back pain (CLBP) are available or currently under development, each associated with different adverse events (AEs) and efficacy profiles. It is therefore important to understand what trade‐offs patients are willing to make when choosing between treatments. Methods: A discrete‐choice experiment (DCE) was conducted with 437 adults with chronic pain caused by OA and/or CLBP. Respondents were presented with a series of scenarios and asked to choose between pairs of hypothetical treatments, each defined by six attributes: level of symptom control; risks of heart attack, rapidly progressive osteoarthritis and dependency; frequency and mode of administration and cost. Attributes were based on known profiles of oral nonsteroidal anti‐inflammatory drugs, opioids and injected nerve growth factor inhibitors, the last of which were under clinical development at the time of the study. Data were analysed using a latent class (LC) model to explore preference heterogeneity. Results: Overall, respondents considered improving symptom control and reducing risk of physical dependency to be the most important attributes. The LC analysis identified four participant classes: an 'efficacy‐focused' class (33.7%), a 'cost‐averse' class (29.4%), a 'physical‐dependence–averse' class (19.6%) and a 'needle‐averse' class (17.3%). Subgroup membership was incompletely predicted by participant age and their responses to comprehension questions. Conclusions: Preference heterogeneity across respondents indicates a need for a personalized approach to offering treatment options. Symptom improvement, cost, physical dependence and route of administration might be important to different patients. Significance: Multiple treatment options that differ substantially in terms of efficacy and adverse events are available for the management of chronic pain. With a growing emphasis on a patient‐centred care model that incorporates patients' priorities and values into treatment decisions, there is a need to understand how individuals with chronic musculoskeletal pain balance the benefits and risks of treatment and how treatment priorities vary among individuals. This study was designed to identify patient preferences for different characteristics of treatments for the management of chronic pain and to investigate how preferences differ among respondents.